2017
DOI: 10.1111/jasp.12496
|View full text |Cite
|
Sign up to set email alerts
|

Dialectical beliefs and savings tendency: Opposite patterns in good versus bad current status

Abstract: People often experience a dilemma: whether we should invest now for a better future or save now for an unexpected future. The current research investigated the influence of dialecticism, a constellation of lay beliefs stating that the world is full of constant changes, coexisting contradictions, and interdependent relationships, on people's savings tendencies when they are with good versus bad status. Study 1 verified that dialectical beliefs were negatively associated with optimistic expectations among people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In contrast, people low in dialectical beliefs perceive that future developments are predictable, there is only one truth, and the elements in the universe are independent and separate. Dialectical beliefs are found to be more prevalent in East Asian societies, but the influence of these lay beliefs is also observed, notably, among people in Western societies (e.g., Ji et al, 2001;Li, 2018;Li et al, 2016;Li et al, 2014;Spina et al, 2010).…”
Section: Dialectical Beliefs and Proenvironmental Behaviorsmentioning
confidence: 98%
See 4 more Smart Citations
“…In contrast, people low in dialectical beliefs perceive that future developments are predictable, there is only one truth, and the elements in the universe are independent and separate. Dialectical beliefs are found to be more prevalent in East Asian societies, but the influence of these lay beliefs is also observed, notably, among people in Western societies (e.g., Ji et al, 2001;Li, 2018;Li et al, 2016;Li et al, 2014;Spina et al, 2010).…”
Section: Dialectical Beliefs and Proenvironmental Behaviorsmentioning
confidence: 98%
“…Ji, Zhang, and Guo (2008) found that people from dialectical cultures were more likely to buy a stock in a declining trend than were their counterparts from nondialectical cultures. Recently, Li (2018) manipulated dialectical beliefs among American participants and observed that dialectical beliefs predicted more consumption of available resources during the present among people in the bad status, which may imply a stronger optimistic prediction on the availability of resources in the future.…”
Section: Dialectical Beliefs and Proenvironmental Behaviorsmentioning
confidence: 99%
See 3 more Smart Citations